论《我与我自己的二三事》归化的翻译策略 = The domestication translation techniques of trivialities about me and myself - 黄楷婷 Wong, Kai Teng (2015)
一部译作的出版除了涉及译者的翻译观与风格，出版社也需要考虑读者市 场的需要以出版足以吸引读者的作品。这些因素都会影响翻译作品所采用的策 略，若译者拥有一定的知名度亦有助于吸引更多读者市场。至今享有“西方首 席汉语翻译家”、“中国当代文学首席翻译家”等美誉的美国著名翻译家葛浩 文历来以翻译中国文学闻名，但鲜为人知的是他也翻译过一些新加坡作家的作 品。 本文将研究葛浩文翻译的新加坡著名华文作家英培安的长篇小说《我与我 自己的二三事》及其译作 Trivialities About Me and Myself，通过结合葛浩文的翻 译观以及作为赞助人的独立出版商 Epigram 所针对的读者市场方针，从目的论 的角度看这部译作如何采用归化的翻译策略，在推广新加坡文化的同时，响应 读者市场的需求。Prior for a translated book to be published, other than just translating the book according to the translator’s point of view and style, the publisher also have to consider the demands of the readers and the market in order to make it attractive. All these factors affect the translation technique used to translate the book. Though certainly, the fame of the translator would have a stronger appeal to the market, thus attracting more readers. Known to the world as The foremost Chinese-English translator in the world and The foremost translator of modern and contemporary Chinese literature in the West, the American born renowned translator Howard Goldblatt has always been popular for his translation of Chinese literature. However, it is not known to many that Howard Goldblatt had also translated Singapore literature works. This paper aims to examine the original Singapore literature novel Trivialities About Me and Myself by local well-known novelist Yeng Pway Ngon and the English translated version by Howard Goldblatt. Using Skopos Theory, while exploring Howard Goldblatt’s view towards translation and the target readers and market of independent publisher, Epigram; this paper will discuss how domestication translation technique was used to translate the novel to promote Singapore’s culture and fulfilling the needs of the readers and market simultaneously.